AKTUALISASI KETERAMPILAN DASAR SEPAKBOLA MURID PUTERA SDN 360 MANIANGPAJO KECAMATAN MANIANGPAJO KABUPATEN WAJO - Andi Rizal; M. Adam Mappaompo; Muhammad Syahrul Saleh (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
This research is a categorical descriptive study regarding the basic football skills of male students at SDN 360 Anabanua, Maniangpajo District, Wajo Regency whose skill level is still uncertain. This research . The aim of the research is to find out and ascertain how good the level of basic football skills of male students at SDN 360 Anabanua District is. Maniangpajo Regency. Wajo. A total of 20 students were sampled. The instrument used was a basic football skills test for 10-12 year olds from Daral Fauzi. includes 6 (six) test items. namely: Dribbing, Short pass, Throw in, Running with the ball, Heading and Shooting at the ball. The data analysis method converts the raw score of each test item into a standard value and then analyzes the percentage to determine the category of basic football skill level. The results of data analysis show that the basic skill level of male students at SDN 360 Ananbanua, District. Maniangpajo, Wajo Regency. defined as “Moderate” calcification.